2010
DOI: 10.1088/0031-9155/55/5/012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two types of adult phantoms in terms of organ doses from diagnostic CT procedures

Abstract: The rapidly increasing number of diagnostic computed tomography (CT) procedures in the recent decades has spurred heightened concern over the potential risk to patients. Although an accurate organ dose assessment tool has now become highly desirable, existing software packages depend on stylized computational phantoms that were originally developed more than 40 years ago, exhibiting very large discrepancies when compared with phantoms that are anatomically realistic. However, past comparative studies did not f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 18 publications
3
27
0
Order By: Relevance
“…The lack of realism offered by stylized phantoms may result in significant discrepancies in the calculated organ doses, ranging from a few per cent to over 100% under certain conditions when compared with image-based voxel phantoms (Chao et al 2001a, 2001b, Zankl et al 2002, Lee et al 2006). For instance, a recent CT dosimetry study by Liu et al (2010) reported a 25% difference between the calculated dose to stylized and voxel phantoms for organs within the scan range. Another major limitation of this study is that the adipose tissues were only positioned at the surface of the stylized phantom and did not account for fat located deep within the abdomen surrounding the internal organs.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of realism offered by stylized phantoms may result in significant discrepancies in the calculated organ doses, ranging from a few per cent to over 100% under certain conditions when compared with image-based voxel phantoms (Chao et al 2001a, 2001b, Zankl et al 2002, Lee et al 2006). For instance, a recent CT dosimetry study by Liu et al (2010) reported a 25% difference between the calculated dose to stylized and voxel phantoms for organs within the scan range. Another major limitation of this study is that the adipose tissues were only positioned at the surface of the stylized phantom and did not account for fat located deep within the abdomen surrounding the internal organs.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] The human body lying on a CT scanner table and helical fan beam x-ray generated from a CT scanner are fully simulated in the computer using the Monte Carlo method.…”
Section: Introductionmentioning
confidence: 99%
“…Estımatıon of Absorbed Dose Dıstrıbutıon in Dıfferent Organs durıng the CT Scan: Monte Carlo Study most accurate, reliable, and versatile in accomplishing this task [1][2][3][4][5][6][7][8].…”
Section: Special Article -Therapeutic Radiologymentioning
confidence: 99%